New aetiology of patellofemoral pain syndrome. (23rd May 2014) - Chas, Julie; Mariot, Philippe; Tassart, Marc; Pialoux, Gilles
Abstract : We report the case of a 30-year-old man with more than 100 different male sexual partners per year. He reported using cocaine, ecstasy, γ-hydroxybutyric acid and crystal mephedrone and presented with bilateral gonalgia resistant to standard analgesia. He had no noteworthy medical history, and physical examination and laboratory tests were uninformative. MRI showed marked intra-articular effusion but no meniscus or ligament damage. The aetiological diagnosis in this case was made by excluding other potential causes. Patellofemoral pain syndrome (PFPS) is one of the most common and challenging injuries. In this first case reported, the aetiology was found to be mechanical, due to the position adopted during fellatio with multiple male partners.